2000
DOI: 10.1177/014920630002600508
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Versus Strategic Reorientation: The Antecedents of Fast-paced Organizational Change

Abstract: We reexamine and extend the antecedents of strategic reorientation, a change in strategy combined with change in at least two of organization structure, power distribution and control systems, presented by Lant, Milliken, and Batra (1992) by using archival data (1987–1993) for firms in the stable furniture and turbulent computer software industries. While enabling direct comparability of results from the two studies, we specify an extended, integrated model of change forces, and test the hypotheses with a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(32 citation statements)
references
References 133 publications
0
28
0
Order By: Relevance
“…Sales growth was selected as the specific measure for performance because this indicator is widely used to measure a firm's success (Boeker and Goodstein, 1993) and can be used as an early warning system for the validity of current strategy (Gordon et al, 2000). Managers' or other stakeholders' dissatisfaction with the firm's performance can act as a catalyst for change and can help to overcome organizational inertia (Boeker, 1997b;Sánchez et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sales growth was selected as the specific measure for performance because this indicator is widely used to measure a firm's success (Boeker and Goodstein, 1993) and can be used as an early warning system for the validity of current strategy (Gordon et al, 2000). Managers' or other stakeholders' dissatisfaction with the firm's performance can act as a catalyst for change and can help to overcome organizational inertia (Boeker, 1997b;Sánchez et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…While the majority of the literature has focussed on analyzing the CEO's involvement in the firm's strategy, some studies have also examined the role of the TMT (Barker et al, 2001;Gordon et al, 2000;Lohrke et al, 2004;Volverda et al, 2001). Some papers argue that senior managerial succession is the primary agent for a change in company strategy (Boyne and Meier, 2009;Gordon et al, 2000;Lant et al, 1992), while other studies suggest the possibility of reciprocal causality between these two elements (Barker et al, 2001). Some authors even believe that these changes are simultaneous (Virany et al, 1992).…”
Section: Patterns Of Strategic Changementioning
confidence: 99%
See 2 more Smart Citations
“…The turbulence of external environments has been shown to influence organizational structure by way of the strategy chosen by companies to manage the dynamics of their market [20]. Subject to the mitigating influence of strategic choices, the extant literature has suggested that successful, highperformance organizations (small and large) in dynamic or turbulent environments tend to have certain structural characteristics [3 13.…”
Section: Structure Environment and Performancementioning
confidence: 99%